Pengaruh Celebrity Endorser, Brand Awareness dan Lifestyle Terhadap Keputusan Pembelian Produk Kecantikan Scarlett Whitening di Kota Banda Aceh - Tuwisna Tuwisna; Tarmizi Gadeng; Ikbal Ramzani P; Nurul Annisa (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to test and analyze the influence of celebrity endorsement, brand awareness and lifestyle on purchasing decisions on Scarlett Whitening beauty products in Banda Aceh. The determination of the research sample uses the Purba formula. The sample used in this study was 96 consumers of Scarlett Whitening beauty products in Banda Aceh and were willing to be respondents. The analysis method applied was multiple linear regression analysis. The results of the study showed that Celebrity endorsement partially had a significant effect on purchasing decisions on Scarlett Whitening beauty products in Banda Aceh. Brand awareness partially had a significant effect on purchasing decisions on Scarlett Whitening beauty products in Banda Aceh. Lifestyle partially had a significant effect on purchasing decisions on Scarlett Whitening beauty products in Banda Aceh. Celebrity endorsement, brand awareness and lifestyle simultaneously had a significant effect on purchasing decisions on Scarlett Whitening beauty products in Banda Aceh.